'I Don't Talk to the Police Except Never': Anna Mendelssohn, Tom Raworth, and Anti-Confessional Life Writing. Issue 1 (9th May 2018) - Savage, Jordan
Abstract : This article begins with a comparative reading of work by Tom Raworth and Anna Mendelssohn. It demonstrates how both poets construct a surface of language that troubles the relationship between reader and poet through perpetual 'turns' which accumulate forms of coherence not reducible to linear arguments or narratives, and also asks the reader to constantly register what forces they apply in order to render meaning in, and through, this surface. In this way, both Raworth and Mendelssohn occupy a defensive position in relation to the reader, and cultivate poetry which 'hovers on the edge of meaning'. Building on this account of a mode of evasiveness which both poets share, grounded in existing Raworth scholarship, the article goes on to focus specifically on Mendelssohn's work. Although both poets take up and problematise life writing, Mendelssohn's is distinct in its relationship to confession, figuring the reader as always potentially an agent of juridical and carceral state power. The article argues that it is this tendency in Mendelssohn's work which warrants its description as 'anti-confessional life writing.'